2020
DOI: 10.1007/s10072-020-04726-6
|View full text |Cite|
|
Sign up to set email alerts
|

REALMS study: real-world effectiveness and safety of fingolimod in patients with relapsing-remitting multiple sclerosis in Portugal

Abstract: Background Fingolimod, an oral sphingosine 1-phosphate receptor modulator, is approved by EMA for relapsing-remitting multiple sclerosis (RRMS). Objectives To assess the effectiveness and safety of fingolimod in patients with RRMS in real-world clinical practice in Portugal. Methods Retrospective, multicentre, non-interventional study, reporting 3 years follow-up of data collected from Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(50 reference statements)
2
5
1
Order By: Relevance
“…Furthermore, some studies employed patients with both progressive and relapsing-remitting disease type [37]. Most of our findings corroborate the outcomes of the biggest real-life studies conducted with fingolimod so far [37,[38][39][40][41][42][43][44][45][46][47][48][49][50][51]56]. Although several papers have been published evaluating the real-world effectiveness of fingolimod, most report outcomes are capped at 2 or 3 years.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, some studies employed patients with both progressive and relapsing-remitting disease type [37]. Most of our findings corroborate the outcomes of the biggest real-life studies conducted with fingolimod so far [37,[38][39][40][41][42][43][44][45][46][47][48][49][50][51]56]. Although several papers have been published evaluating the real-world effectiveness of fingolimod, most report outcomes are capped at 2 or 3 years.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, apart from a select few [32,37,38], most of the studies examining fingolimod in a real-world practice published so far are heterogeneous in terms of the methodologies and/or the cohorts used. Some of them were conducted solely in a single centre [30,[39][40][41][42][43], some of them were posthoc analyses of the pivotal studies [44][45][46], some used a relatively small cohort [30,39,40,43,47,48]. Meanwhile, others have focused only on a single objective [49][50]; except a few studies [51,52], the follow-up period was surprisingly brief [43,[53][54][55] in several reports.…”
Section: Discussionmentioning
confidence: 99%
“…Within 6 h of the first dose, 19 patients experienced bradycardia, which was symptomatic in two; six patients had a second‐degree AV block, and one developed a third‐grade AV block 104 . Similar rates were also observed in other long‐term real‐world studies 105,106 …”
Section: Risk Of Cardiac Conduction Abnormalities With Smdssupporting
confidence: 89%
“…104 Similar rates were also observed in other long-term realworld studies. 105,106 Siponimod selectively modulates S1P1 and S1P5 receptors, and it is approved for the treatment of multiple sclerosis. 107 A phase 3, placebo-controlled RCT in which 1105 patients with multiple sclerosis were randomised to receive treatment with siponimod 2 mg or placebo.…”
Section: Evidence From Non-ibd Imids Studiesmentioning
confidence: 99%
“…A long-term follow-up study by Healy et al found that interferon-beta (IFN-β) could appropriately extend the time for EDSS to reach 4 points and 6 points ( 11 ). Batista et al showed that fingolimod could significantly reduce the ARR of MS patients, and that the EDSS score remained stable during the use of fingolimod ( 12 ). Teliflunomide has a good effect on patients with mild disabilities (EDSS ≤ 2) initial treatment ( 13 ).…”
Section: Discussionmentioning
confidence: 99%